2015
DOI: 10.1007/s00441-015-2299-0
|View full text |Cite
|
Sign up to set email alerts
|

Brief sensory experience differentially affects the volume of olfactory brain centres in a moth

Abstract: Experience modifies behaviour in animals so that they adapt to their environment. In male noctuid moths, Spodoptera littoralis, brief pre-exposure to various behaviourally relevant sensory signals modifies subsequent behaviour towards the same or different sensory modalities. Correlated with a behavioural increase in responses of male moths to the female-emitted sex pheromone after pre-exposure to olfactory, acoustic or gustatory stimuli, an increase in sensitivity of olfactory neurons within the primary olfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Brief exposures to odors were previously shown to impact the expression of olfactory receptors, odorant binding proteins, and the development of brain olfactory centers in honeybees and moths (3134). In the bee, qRT-PCR analysis revealed that 6 floral scent receptors were differentially expressed in the antenna depending on the scent environment they experienced (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brief exposures to odors were previously shown to impact the expression of olfactory receptors, odorant binding proteins, and the development of brain olfactory centers in honeybees and moths (3134). In the bee, qRT-PCR analysis revealed that 6 floral scent receptors were differentially expressed in the antenna depending on the scent environment they experienced (31).…”
Section: Discussionmentioning
confidence: 99%
“…In the bee, qRT-PCR analysis revealed that 6 floral scent receptors were differentially expressed in the antenna depending on the scent environment they experienced (31). A brief one-minute exposure of male moths to female sex pheromones led to the up-regulation of a pheromone-binding protein in the male antennae, an enlargement of the antennal lobe, and an increase in the volume of the mushroom bodies in the male brain, which resulted in a higher sensitivity of the exposed males to the female blend (3234). The brief exposure of B. anynana females to the new male pheromone blend may have led to similar changes in the female brain.…”
Section: Discussionmentioning
confidence: 99%
“…In insects, various behaviors are modulated in response to physiological or environmental changes, such as experience, mating, age or time of the day (review in Martel et al, 2009). In most species, this behavioral plasticity is mainly sustained by a modulation of the central olfactory system (antennal lobes and mushroom bodies, see e.g., Barrozo et al, 2011;Anton et al, 2015). But as antennae are the first place of odorant detection, modulation can also take place at this peripheral level.…”
Section: Discussionmentioning
confidence: 99%
“…littoralis is modified by brief pre-exposure, eliciting increased sensitivity of peripheral and more pronouncedly in AL neurons as well as an increase in the volume of the pheromone-processing cumulus of the macroglomerular complex within the antennal lobe and the calyces of the secondary olfactory centres, the mushroom bodies [25, 27, 28], nothing is known so far on the neuromodulators potentially involved in these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Such a type of olfactory plasticity based on non-associative learning has been unveiled in the moth Spodoptera littoralis : a brief pre-exposure to sex pheromone enhances behavioural responses to sex pheromone 15 min and 24 h later [25, 26]. Pheromone exposure was also shown to enhance peripheral pheromone detection, central nervous pheromone responses, and to induce an increase in the volume of certain glomeruli and specifically the size of the biggest glomerulus processing the main pheromone component within the antennal lobe (AL), the primary olfactory centre, as well as in a secondary olfactory centre, the calyces of the mushroom bodies [25, 27, 28]. It is so far unknown if such pre-exposure effects are also present in other insects and if they depend on the physiological state of the insect.…”
Section: Introductionmentioning
confidence: 99%